Sustaining food production for food security: a case study for Federal Agricultural Marketing Authority (FAMA) / Anies Farahin Abdul Rahman and Siti Shakiroh Ahmad Tajudin - Abdul Rahman, Anies Farahin; Ahmad Tajudin, Siti Shakiroh (Faculty of Business and Management, 2013)
Food security issue is getting more attention by world today. Increase in population getting more unbalance with the nation food production causing most of the third world country facing food security threat. Malaysia is one of the many countries in our planet, tiny though it is, where food self-sufficiency is decreasing, year by year. The weakness of the Malaysia agricultural sector is that it largely produces cash crops and little food. Government agencies and agri-entrepreneurs as well as individual farmers are equally important in ensuring sufficient and quality food supply in Malaysia. Federal Agricultural Marketing Authority (FAMA) is one of the leading agency under the Ministry of Agriculture and Agro-based Industry that involves in extension activities in food production. This paper briefly describes the current extension programs undertaken by Federal Agricultural Marketing Authority (FAMA) in food production system from farm to consumer. These programs have encouraged local farmers and agri-entrepreneurs to increase their food production to meet local and world demand. As a marketing agency, in order for FAMA to overcome food production crisis, they have planned their marketing mix strategies and supply chain management effectively.